Addiction Topics in Counselor Educator Professional Development: A Content Analysis. Issue 1 (April 2016) - Moro, Regina R.; Wahesh, Edward; Likis‐Werle, S. Elizabeth; Smith, Jayne E.
Abstract : Counselor educators prepare master's‐level counselors‐in‐training on addiction topics. This content analysis examined the frequency and types of addiction topics for counselor educator continuing education. The results revealed limited attention to addiction topics within professional literature and conference presentations.